Development and validation of a scale for measuring students' mathematics-related beliefs - Çayır, Ayşegül Kamer Yıldırım. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
This study aimed to develop and validate a scale based on a framework of students’ mathematics related beliefs. Several models have been proposed to explain this rather extensive construct. The framework used in this study was based on the existing models in the literature to explain students’ mathematics related beliefs. The framework included students’ beliefs about mathematics education, students’ beliefs about self and students’ beliefs about social context. The categories of the framework were divided into dimensions for scale development. The scale was developed to cover the dimensions as students beliefs about (1) the nature of mathematics, (2) learning and problem solving, (3) teaching; (4) self efficacy, (5) control, (6) task-value, (7) goal-orientation, (8) social norms, (9) socio-mathematical norms. Data on 300 8th grade students were analyzed to assess the psychometric qualities of the instrument, to assess model fit to the framework, to describe students’ math related beliefs, and to investigate gender differences and the relationship between mathematics achievement and beliefs. The instrument was found to be reliable and valid. The data provided empirical evidence for a modified model on the framework. Students’ beliefs indicated a desirable direction. There were no gender differences except on the first subscale of students’ beliefs about the nature of mathematics. The relation between beliefs about social context and mathematics achievement were found to be statistically significant.
Keywords: Mathematics -- Study and teaching.